Silicate ceramic material with multicolor reversible photochromic performance as well as preparation method and application of silicate ceramic material
By doping transition metal ions regulated BaMgSiO4:xTM silicate ceramic material, the problem of limited types and insufficient performance of inorganic photochromic materials is solved, and multi-color reversible photochromic performance is achieved, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411807237.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-28
AI Technical Summary
The existing types of inorganic photochromic materials are limited, and their physical and chemical stability and fatigue resistance are insufficient, which limits their practical application value.
A silicate ceramic material of BaMgSiO4:xTM is used to adjust the photochromic properties of the material by doping transition metal ions (such as Co, Cr, Fe, Ni, Cu) to prepare a multi-color reversible photochromic material. The material is prepared by pre-sintering, tableting, detachment and sintering, and has good stability and fatigue resistance.
The multi-color reversible photochromic properties are achieved. The material can change its color under ultraviolet light and restore its original state through heat treatment, which solves the problems of low discoloration efficiency and lack of color in existing materials. It has high stability and fatigue resistance and is suitable for a variety of application scenarios.
Smart Images

Figure CN119528560A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to inorganic photochromic material technology, in particular to a silicate ceramic material with multi-color reversible photochromic properties, a preparation method and an application thereof. Background Art
[0002] Reversible photochromism refers to the change of color of a material under the stimulation of light of a specific wavelength, and can be restored to its original state by light stimulation of another wavelength or heat stimulation, thus achieving a reversible change between two different states. Photoresponsive smart materials have broad application prospects in many fields: such as light modulation devices, readable and writable optical information storage and recording, memory elements, protective camouflage, coating industry, radiation measurement, etc.
[0003] At present, the research on organic compound photochromic materials has developed rapidly and has achieved fruitful results, but there are also the following problems of organic photochromic materials, such as poor firmness and stability, easy oxidation, easy deactivation of color change performance, poor fatigue resistance, and great environmental pollution during the preparation process. Inorganic photochromic materials have high physical and chemical stability, long color change time, and good fatigue resistance, but so far, the development of inorganic photochromic materials is very slow and their types are very limited, which largely limits the practical application value of inorganic photochromic materials. Summary of the invention
[0004] The purpose of the present invention is to provide a silicate ceramic material with multi-color reversible photochromic properties, a preparation method and an application thereof in view of the deficiencies of the prior art. The material has low raw material cost, low equipment requirements, and good fatigue resistance. It can be applied to optical information storage, light regulation, optical device materials, sensors, anti-counterfeiting, self-developing holographic recording photography, decoration, radiation meter and protective packaging materials. The preparation process of this method is simple and easy, with good repeatability and high stability of the obtained product.
[0005] The technical solution for achieving the purpose of the present invention is: A silicate ceramic material with multi-color reversible photochromic properties, the chemical formula of the silicate material is BaMgSiO 4 :xTM, wherein TM is a transition metal ion, TM is one or more of Co, Cr, Fe, Ni, Cu, x is the doping molar amount of TM, 0≤x≤0.1.
[0006] A method for preparing the above-mentioned multi-color reversible photochromic silicate ceramic material, the method comprising: mixing a Ba-containing compound, a Mg-containing compound, a Si-containing compound and a Tm-containing compound, performing pre-sintering, tableting, debonding, a first sintering and a second sintering to obtain a multi-color reversible photochromic silicate material, wherein the molar ratio of Ba, Mg, Si and Tm in the Ba-containing compound, the Mg-containing compound, the Si-containing compound and the TM-containing compound is 1:1:1:x; 0≤x≤0.1.
[0007] The Ba-containing compound is one or more of Ba carbonate, Ba nitrate and Ba oxide, more preferably Ba carbonate; the Mg-containing compound is one or more of Mg oxide, Mg carbonate and Mg nitrate, more preferably Mg oxide; the Si-containing compound is one or more of Si oxide, Si carbonate and Si nitrate, more preferably Si oxide; the Tm-containing compound is one or more of Tm carbonate, TM nitrate and TM oxide, more preferably TM oxide and carbonate.
[0008] The pre-firing temperature is 1000-1300° C., and the pre-firing holding time is 2-3 hours. The preferred temperature is 1100° C., and the preferred pre-firing time is 2 hours.
[0009] The tabletting pressure is 4-6 MPa, and the tabletting diameter is 13-15 mm. The preferred pressure is 6 MPa, and the preferred tabletting diameter is 15 mm.
[0010] The debonding temperature is 400-600° C., and the debonding time is 8-10 hours, preferably 550° C. and 10 hours.
[0011] The first sintering temperature is 1100-1400° C., the sintering time is 3-6 hours, the sintering atmosphere is air, and the temperature is selected to be 1350° C. for 4 hours.
[0012] The second sintering temperature is 1200-1500°C, and the sintering atmosphere is a reducing atmosphere, wherein 5% H 2 、95%N 2 , preferably 1350°C, 4h.
[0013] The silicate ceramic material with multi-color reversible photochromic performance is prepared by the preparation method.
[0014] The application of silicate ceramic materials with multi-color reversible photochromic properties in reversible photochromic products is to irradiate the silicate materials with corresponding ultraviolet light and then perform heat treatment. The applications are applied to optical information storage, light regulation, optical device materials, sensors, anti-counterfeiting, self-developing holographic recording photography, decoration, radiation meters and protective packaging materials.
[0015] In the technical solution, the base color of the sample without doped elements is white, which will change from white to pink after being irradiated with 265nm ultraviolet light. Since the doped elements themselves have colors, the doped samples have non-white (blue, green, purple) chemical colors. After the photochromic material with the matrix chemical color is irradiated with 265nm ultraviolet light, its photochromic color will form a composite color (gray, brown, gray-black) superimposed by the matrix color and pink, and after corresponding ultraviolet irradiation and high-temperature treatment, it will return to the original matrix structural color.
[0016] This technical solution solves the problems of low color change efficiency and lack of color change colors of current photochromic materials. This technical solution uses the adjustment of the doping amount of TM to control the matrix color and color change degree of the photochromic material, and obtains a type of inorganic multicolor reversible photochromic material, whose color changes from the matrix color (blue, green, purple, pink) to the corresponding composite color (gray, brown, black) under the irradiation of ultraviolet light, and its composite color can be restored to the matrix color under the irradiation of ultraviolet light of the corresponding band or after heat treatment.
[0017] This material has low raw material cost and low equipment requirements, and has the advantages of good fatigue resistance. It can be used in optical information storage, light regulation, optical device materials, sensors, anti-counterfeiting, self-developing holographic recording photography, decoration, radiation meters and protective packaging materials. This method has a simple preparation process, good repeatability, and the resulting product has high stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The undoped BaMgSiO prepared in Example 1 4 Diffuse reflectance spectra before and after irradiation at 265 nm; Figure 2 The Co-doped BaMgSiO prepared in Example 2 4 Diffuse reflectance spectra before and after irradiation at 265 nm; Figure 3 The Cr-doped BaMgSiO prepared in Example 3 4 Diffuse reflectance spectra before and after irradiation at 265 nm; Figure 4 The Fe-doped BaMgSiO prepared in Example 4 4 Diffuse reflectance spectra before and after irradiation at 265 nm; Figure 5 The Ni-doped BaMgSiO prepared in Example 5 4 Diffuse reflectance spectra before and after irradiation at 265 nm; Figure 6The Cu-doped BaMgSiO prepared in Example 6 4 Diffuse reflectance spectra before and after irradiation at 265 nm. DETAILED DESCRIPTION
[0019] The content of the present invention is further described below in conjunction with the drawings and embodiments, but the present invention is not limited thereto.
[0020] Example 1: BaCO was weighed in a molar ratio of 1:1:1 3 , MgO and SiO 2 , and then fully mix and grind to obtain a uniform mixed solid powder. The obtained mixed solid powder is placed in a corundum crucible, placed in a high-temperature furnace, heated to 1100°C at a heating rate of 5°C / min, and kept warm for 4 hours for pre-sintering; the calcined product is naturally cooled to room temperature and then taken out and ground again, and pressed into tablets by a powder tablet press at a pressure of 6MPa; the pressed tablets are placed in a crucible and placed in a muffle furnace, heated to 550°C at a heating rate of 1°C / min, and kept warm for 10 hours for debonding; the debonded sample is placed in a muffle furnace and a reducing gas (5%H 2 +95%N 2 ), the temperature was raised to 1350°C at a heating rate of 5°C / min and kept at this temperature for 4 h to obtain a reversible photochromic ceramic material with a white surface color. The prepared non-ion-doped BaMgSiO 4 The diffuse reflectance spectra of reversible photochromic ceramic materials after UV excitation and corresponding UV irradiation or high temperature treatment are as follows: Figure 1 As shown in the figure, the results show that the non-ion-doped BaMgSiO 4 Reversible photochromic ceramic materials change from white to light red under ultraviolet light, and return to their original white under corresponding ultraviolet light or high temperature conditions.
[0021] Example 2: BaCO was weighed at a molar ratio of 0.995:1:1:0.001667 3 、MgO、SiO 2 and Co 3 O 4Then, the mixture was fully mixed and ground to obtain a uniform mixed solid powder. The mixed solid powder was placed in a corundum crucible, placed in a high-temperature furnace, heated to 1100°C at a heating rate of 5°C / min, and kept warm for 4 hours for pre-sintering. The calcined product was naturally cooled to room temperature, taken out and ground again, and pressed into tablets by a powder tablet press at a pressure of 6MPa. The pressed tablets were placed in a crucible and placed in a muffle furnace, heated to 550°C at a heating rate of 1°C / min, and kept warm for 10 hours for debonding. The debonded sample was placed in a muffle furnace, air was introduced, and the temperature was increased to 1350°C at a heating rate of 5°C / min, and kept warm for 4 hours for the first sintering. The sample after the first sintering was placed in a muffle furnace, and reducing gas (5%H 2 +95%N 2 ), the temperature was raised to 1350°C at a heating rate of 5°C / min, and the temperature was kept for 4 hours for the second sintering to obtain a reversible photochromic ceramic material with a blue surface color. The diffuse reflectance spectra of the prepared Co ion-doped silicate reversible photochromic ceramic material after ultraviolet light excitation and the corresponding ultraviolet light or high temperature treatment are as follows Figure 2 As shown, the results show that the Co ion-doped silicate reversible photochromic ceramic material prepared by the method of this example changes from matrix blue to composite gray under ultraviolet light, and returns to the original blue under corresponding ultraviolet light or high temperature conditions.
[0022] Example 3: BaCO was weighed at a molar ratio of 0.95:1:1:0.025. 3 、MgO、SiO 2 and Cr 2 O 3 Then, the mixture was fully mixed and ground to obtain a uniform mixed solid powder. The mixed solid powder was placed in a corundum crucible, placed in a high-temperature furnace, heated to 1100°C at a heating rate of 5°C / min, and kept warm for 4 hours for pre-sintering. The calcined product was naturally cooled to room temperature and then taken out and ground again. The powder tablet press was used to press the tablets at a pressure of 6MPa. The pressed tablets were placed in a crucible and placed in a muffle furnace. The temperature was increased to 550°C at a heating rate of 1°C / min, and kept warm for 10 hours for debonding. The debonded sample was placed in a muffle furnace and a reducing gas (5%H 2 +95%N 2 ), the temperature was raised to 1350°C at a heating rate of 5°C / min, and the temperature was kept for 4 hours for sintering to obtain a reversible photochromic ceramic material with a green surface color. The diffuse reflectance spectra of the prepared Cr ion-doped silicate reversible photochromic ceramic material after ultraviolet light excitation and the corresponding ultraviolet light or high temperature treatment are as follows Figure 3As shown, the results show that the Cr ion-doped silicate reversible photochromic ceramic material prepared by the method of this example changes from matrix green to composite brown under ultraviolet light, and returns to the original green under corresponding ultraviolet light or high temperature conditions.
[0023] Example 4: BaCO was weighed at a molar ratio of 0.95:1:1:0.025. 3 、MgO、SiO 2 and Fe 2 O 3 Then, the mixture was fully mixed and ground to obtain a uniform mixed solid powder. The mixed solid powder was placed in a corundum crucible, placed in a high-temperature furnace, heated to 1100°C at a heating rate of 5°C / min, and kept warm for 4 hours for pre-sintering. The calcined product was naturally cooled to room temperature and then taken out and ground again. The powder tablet press was used to press the tablets at a pressure of 6MPa. The pressed tablets were placed in a crucible and placed in a muffle furnace. The temperature was increased to 550°C at a heating rate of 1°C / min, and kept warm for 10 hours for debonding. The debonded sample was placed in a muffle furnace and a reducing gas (5%H 2 +95%N 2 ), the temperature was raised to 1350°C at a heating rate of 5°C / min, and the temperature was kept for 4 hours for sintering to obtain a reversible photochromic ceramic material with a milky white surface color. The diffuse reflectance spectra of the prepared Fe ion-doped silicate reversible photochromic ceramic material after ultraviolet light excitation and the corresponding ultraviolet light or high temperature treatment are as follows Figure 4 As shown, the results show that the Cr ion-doped silicate reversible photochromic ceramic material prepared by the method of this example changes from white to red under ultraviolet light, and returns to its original white under corresponding ultraviolet light or high temperature conditions.
[0024] Example 5: BaCO was weighed in a molar ratio of 0.99:1:1:0.01 3 、MgO、SiO 2 and NiO and then fully mixed and ground to obtain a uniform mixed solid powder, the obtained mixed solid powder was placed in a corundum crucible, placed in a high-temperature furnace, heated to 1100°C at a heating rate of 5°C / min, and kept warm for 4 hours for pre-sintering; the calcined product was naturally cooled to room temperature and then taken out and ground again, and pressed into tablets by a powder tablet press at a pressure of 6MPa; the pressed tablets were placed in a crucible and placed in a muffle furnace, heated to 550°C at a heating rate of 1°C / min, and kept warm for 10 hours for debonding; the debonded sample was placed in a muffle furnace, and a reducing gas (5%H 2 +95%N 2), the temperature was raised to 1350℃ at a heating rate of 5℃ / min, and the temperature was kept for 4h for sintering to obtain a reversible photochromic ceramic material with a gray-purple surface color. The diffuse reflectance spectra of the prepared Fe ion-doped silicate reversible photochromic ceramic material after ultraviolet light excitation and the corresponding ultraviolet light or high temperature treatment are as follows Figure 5 As shown, the results show that the Ni ion-doped silicate reversible photochromic ceramic material prepared by the method of this example changes from purple to gray-black under ultraviolet light, and returns to the original purple under corresponding ultraviolet light or high temperature conditions.
[0025] Example 6: BaCO was weighed in a molar ratio of 0.99:1:1:0.01 3 、MgO、SiO 2 and CuO and then fully mixed and ground to obtain a uniform mixed solid powder. The obtained mixed solid powder was placed in a corundum crucible, placed in a high-temperature furnace, heated to 1100°C at a heating rate of 5°C / min, and kept warm for 4 hours for pre-sintering; the calcined product was naturally cooled to room temperature and then taken out and ground again, and pressed into tablets by a powder tablet press at a pressure of 6MPa; the pressed tablets were placed in a crucible and placed in a muffle furnace, heated to 550°C at a heating rate of 1°C / min, and kept warm for 10 hours for debonding; the debonded sample was placed in a muffle furnace and a reducing gas (5%H 2 +95%N 2 ), the temperature was raised to 1350°C at a heating rate of 5°C / min, and the temperature was kept for 4 hours for sintering to obtain a reversible photochromic ceramic material with a gray surface color. The diffuse reflectance spectra of the prepared Cu ion-doped silicate reversible photochromic ceramic material after ultraviolet light excitation and the corresponding ultraviolet light or high temperature treatment are as follows Figure 6 As shown, the results show that the Cu ion-doped silicate reversible photochromic ceramic material prepared by the method of this example changes from grayish white to light red under ultraviolet light, and returns to its original grayish white under corresponding ultraviolet light or high temperature conditions.
Claims
1. A silicate ceramic material with multi-color reversible photochromic properties, characterized in that: The chemical formula of the silicate material is BaMgSiO4:xTM, wherein TM is a transition metal ion, TM is one or more of Co, Cr, Fe, Ni, and Cu, and x is the doping molar amount of TM, 0≤x≤0.
1.
2. A method for preparing a silicate ceramic material with multi-color reversible photochromic properties as claimed in claim 1, characterized in that: The method comprises: mixing a Ba-containing compound, a Mg-containing compound, a Si-containing compound and a TM-containing compound, and performing pre-sintering, tableting, debonding, first sintering and second sintering to obtain a multi-color reversible photochromic silicate material, wherein the molar ratio of Ba, Mg, Si and Tm in the Ba-containing compound, the Mg-containing compound, the Si-containing compound and the TM-containing compound is 1:1:1:x; 0≤x≤0.
1.
3. The method for preparing a silicate ceramic material with multi-color reversible photochromic properties according to claim 2, characterized in that: The Ba-containing compound is one or more of Ba carbonate, Ba nitrate and Ba oxide; the Mg-containing compound is one or more of Mg oxide, Mg carbonate and Mg nitrate; the Si-containing compound is one or more of Si oxide, Si carbonate and Si nitrate; the TM-containing compound is one or more of TM carbonate, TM nitrate and TM oxide.
4. The method for preparing a silicate ceramic material with multi-color reversible photochromic properties according to claim 2, characterized in that: The pre-firing temperature is 1000-1300° C. and the pre-firing insulation time is 2-3 hours.
5. The method for preparing a silicate ceramic material with multi-color reversible photochromic properties according to claim 2, characterized in that: The tabletting pressure is 4-6 MPa, and the tabletting diameter is 13-15 mm.
6. The method for preparing a silicate ceramic material with multi-color reversible photochromic properties according to claim 2, characterized in that: The debonding temperature is 400-600° C., and the debonding time is 8-10 hours.
7. The method for preparing a silicate ceramic material with multi-color reversible photochromic properties according to claim 2, characterized in that: The temperature of the first sintering is 1100-1400° C., the sintering time is 3-6 hours, and the sintering atmosphere is air.
8. The method for preparing a silicate ceramic material with multi-color reversible photochromic properties according to claim 2, characterized in that: The temperature of the second sintering is 1200-1500°C, and the sintering atmosphere is a reducing atmosphere with a composition of 5% H2+95% N2.
9. A silicate ceramic material with multi-color reversible photochromic properties prepared by the preparation method according to claim 2.
10. The use of the multi-color reversible photochromic silicate ceramic material according to claim 9 in a reversible photochromic product, characterized in that: The silicate material is irradiated with corresponding ultraviolet light and then heat treated. The application is in optical information storage, light regulation, optical device materials, sensors, anti-counterfeiting, self-developing holographic recording photography, decoration, radiation meter and protective packaging materials.